Utility of Voiding Dysfunction Symptom Score in Diagnosis and Treatment of Enuresis Nocturna - ŞEKERCİ, ÇAĞRI AKIN; ŞİMŞEK, FERRUH; TARCAN, TUFAN; ŞENER, TARIK EMRE; TANIDIR, YILÖREN (GALENOS YAYINCILIK, 2017)
Objective: The aim of this study was to determine the effectiveness of the voiding dysfunction symptom score (VDSS) in evaluation of children with nocturnal enuresis. Materials and Methods: Four hundred children with nocturnal enuresis were included in the study. They were evaluated with VDSS, physical examination, urinalysis and 2-day voiding diary. All children with nocturnal enuresis symptoms were treated with desmopressin and/or urotherapy. However, children with overactive bladder symptoms were also treated with anticholinergics. Treatment success and change in VDSS were compared and assessed between different treatment methods. Results: Two hundred forty-five children (61.25%) were male and 155 (38.75%) were female. The mean age was 7.6 +/- 3.0 years (range: 5-18). The mean VDSS was 9.2 +/- 6.3. 35% of children with nocturnal enuresis had concomitant daytime symptoms. 126 children (31.5%) had a VDSS of nine or above and majority of these children were treated with anticholinergic therapy. VDSS questionnaire could not help determine treatment success in children with non-monosymptomatic nocturnal enuresis. However, children treated with urotherapy and desmopressine showed significant difference in VDSSs according to their treatment response. Conclusion: VDSS has shown to decrease after treatment in children with mono-symptomatic nocturnal enuresis. The treatment strategies should be checked and modified if VDSS does not decrease after proper therapy as this would increase the success of treatment.
Keywords: Symptom score; voiding dysfunction; urotherapy; enuresis nocturna; desmopressin; CHILDREN; DESMOPRESSIN; STANDARDIZATION; ADOLESCENTS; PREVALENCE; CHILDHOOD; SYSTEM